2014
DOI: 10.1080/14786419.2014.927874
|View full text |Cite
|
Sign up to set email alerts
|

Didemnacerides A and B: two new glycerides from Red Sea ascidian Didemnum species

Abstract: Two new glycerides, didemnacerides A (1) and B (2), together with three known sterols, 24-ethyl-25-hydroxycholesterol (3), cholest-6-en-3,5,8-triol (4) and cholestane-3β,5α,6β-26-tetrol (5), were isolated from the Red Sea ascidian Didemnum sp. Their structures were elucidated by using extensive 1D ((1)H, (13)C) and 2D ((1)H-(1)H COSY, HSQC and HMBC) NMR studies and mass spectroscopic data (GC-MS and HR-MS) as well as alkaline hydrolysis followed by GC-MS and NMR spectral analyses of the fatty acid methyl ester… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 36 publications
(39 reference statements)
0
5
0
Order By: Relevance
“…The 22 new tunicate-derived natural products presented in this review is the second lowest number reported in one year over the last decade. A structurally-diverse range of metabolites were reported, with examples of glycerides 1314 and 1315, 832 amino alcohols 1316-1322, 833 new didemnaketal congeners 1323, 1324 834 and 1325, 1326, 835 halogenated alkaloids 1327 and 1328, 836 a new rubrolide (R) 1329 837 (that unfortunately shares the same letter designation as a related metabolite reported from Aspergillus terreus 217 ), pyridoacridine cnemidine A 1330 552 and sulfated sterols 1331 and 1332. 838 Noteworthy was the isolation, structure elucidation and synthesis of a rare example of a modied nucleoside bearing a 5 0 -thiomethyl substituent 1333.…”
Section: Molluscsmentioning
confidence: 99%
“…The 22 new tunicate-derived natural products presented in this review is the second lowest number reported in one year over the last decade. A structurally-diverse range of metabolites were reported, with examples of glycerides 1314 and 1315, 832 amino alcohols 1316-1322, 833 new didemnaketal congeners 1323, 1324 834 and 1325, 1326, 835 halogenated alkaloids 1327 and 1328, 836 a new rubrolide (R) 1329 837 (that unfortunately shares the same letter designation as a related metabolite reported from Aspergillus terreus 217 ), pyridoacridine cnemidine A 1330 552 and sulfated sterols 1331 and 1332. 838 Noteworthy was the isolation, structure elucidation and synthesis of a rare example of a modied nucleoside bearing a 5 0 -thiomethyl substituent 1333.…”
Section: Molluscsmentioning
confidence: 99%
“…Soft corals were classified as; Heteroxenia fuscescens, didemnum moseleyi, Lobophytum pauciflorum, Sarcophyton trocheliophorum and Sinularia spp. which was reported by Ibrahim et al (2014), Afifi et al (2016), Hassan et al (2016), Tarek et al (2016) and Zubair et al (2016), . Sponges were classified to: Ircinia strobilina, Callyspongia viridis, Suberea spp, Spongia officinalis and Biemna ehrenbergi, this was reported by Ilan et al (2004), El-Ganainy et al (2005, Mohamed et al (2014) and Almohammadi (2017) (2014) .…”
Section: Discussionmentioning
confidence: 61%
“…The known metabolites M0 and M1 are identified as PD (R) and PD (S), respectively. M2, 3β,21α,22β-hydroxy-24-norolean-12-ene; M3, 5α,8α-dihydroxycholest-6-en-3β-ol; M4, (3β,12β,24S)-20,24-epoxydammar-25-ene-3,12-diol; M5, (3β,4β,22β)-olean-12-ene-3,22,23-triol; M6, soyasapogenol E. The NMR spectra are in good agreement with those reported. ,…”
Section: Resultsmentioning
confidence: 73%